Design, build and fly the UiTM’s vertical take-off and landing (VTOL) aircraft / Zurriati Mohd Ali, Muhammad Izzat Izzudin Jefri and Zulhilmy Sahwee - Mohd Ali, Zurriati; Jefri, Muhammad Izzat Izzudin Jefri; Sahwee, Zulhilmy (Universiti Teknologi MARA, 2023)
The aircraft with a vertical take-off and landing (VTOL) technology has been widely studied all around the world as it is one of the most advanced systems that could be used by modern aircraft. It was invented for any types of simple multirotor aircraft to a more complex transitioning vehicle. In this project, the vertical take-off and landing (VTOL) radio-controlled (RC) aircraft were designed, build, and test. The USB-based microcontroller, Teensy 4.0 board will be incorporated into this aircraft to control the varying multirotor thrust vector to lift the aircraft. The design of the aircraft was inspired by the Fighter Jet Sukhoi SU-30. It was designed through CAD drawing using the CATIA software. From the CAD drawing, the aircraft then was fabricated and installed with the electronic devices. Through the electronic devices, the tilt angles of the rotors need to be changed smoothly and steadily using the coding inside the Arduino software before they can be inserted into the Teensy 4.0 programming to ensure the stability of the aircraft during take-off and landing. The RC aircraft then went through a few flights test to get the performance data of the aircraft such as the maximum speed, the rate of climbing and landing, and the hovering stability. The size of the VTOL RC is 0.84 meters in length,0.58 meters in the width, and a height of 0.32 meters. The VTOL RC aircraft were successfully designed and fabricated.